SPE Asia Pacific Oil and Gas Conference and Exhibition 2013
DOI: 10.2118/165796-ms
|View full text |Cite
|
Sign up to set email alerts
|

Prehydrating High-strength Microspheres in Lightweight Cement Slurry Creates Value for Offshore Malaysian Operator

Abstract: Casing cementation across depleted reservoirs can be challenging because conventionally weighted cement slurries can induce losses and damage the permeability of formations caused by the higher associated hydrostatic pressure they exert on the wellbore. Therefore, when such pressure-related concerns exist, lighter-weight cement slurries are often preferred. For an offshore Malaysia operator, a lightweight cement slurry was proposed to reduce hydrostatic pressure and prevent losses and formation damage. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Some of these researches are presented in Table 1. Mavares and Pertuz [4] and Abdullah et al [5] attempted to design slurries for cementing wells that go through formations with low fracture gradients. Both fulfilled the requirements involved in this application with the addition of HGMS in proportions ranging from 12% to 20% by weight of cement (bwoc).…”
Section: █ Introductionmentioning
confidence: 99%
“…Some of these researches are presented in Table 1. Mavares and Pertuz [4] and Abdullah et al [5] attempted to design slurries for cementing wells that go through formations with low fracture gradients. Both fulfilled the requirements involved in this application with the addition of HGMS in proportions ranging from 12% to 20% by weight of cement (bwoc).…”
Section: █ Introductionmentioning
confidence: 99%
“…The authors recorded TT that ranged between 51-430 min and CS ranges between 420-2530 psi. Abdullah et al (2013) also reported a CS of 752 and 1405 psi after curing for 24 and 48h, respectively for a neat cement system. Although the average CS of 614 psi obtained in this present study is lower yet, CS higher than the formation pressure could fracture the formation.…”
Section: Multi-objective Function Optimization Studiesmentioning
confidence: 84%
“…A good cement job ensures efficient zonal isolation and protection of casing. , Based on prevailing wellbore conditions and cementing objectives, different admixtures are incorporated into the cement slurry design to achieve an efficient cement bond . Cement slurries prepared with just water and cement, commonly known as neat cement, may have densities in the range of 15.6–16.4 ppg . In low fracture gradient formations, high hydrostatic pressure as a result of increased cement slurry density could result in formation breakdown and subsequent loss of circulation .…”
Section: Introductionmentioning
confidence: 99%